2023
DOI: 10.1021/acssensors.2c02602
|View full text |Cite
|
Sign up to set email alerts
|

Sensing Technologies for Extravasation Detection: A Review

Abstract: Peripheral intravenous catheters are administered for various purposes, such as blood sampling or the infusion of contrast agents and drugs. Extravasation happens when the catheter is unintentionally directed outside of the vein due to movement of the intravascular catheter, enhanced vascular permeability, or occlusion of the upstream vein. In this article, extravasation and its mechanism are discussed. Subsequently, the sensorized devices (e.g., single sensor and multimodal detection) to identify the extravas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Furthermore, clinical examination of signs and symptoms may not be sensitive enough to detect cases of infiltration and extravasation in earlier stages. Alternatively, the use of technologies including ultrasound may be useful for early detection of infiltration and extravasation [68]. A study of PIVC failure in adults found that 9.7% of participants presented with subcutaneous edema on clinical exam, versus 56.5% of participants based on ultra sonographic evaluation [18].…”
Section: Diagnosismentioning
confidence: 99%
“…Furthermore, clinical examination of signs and symptoms may not be sensitive enough to detect cases of infiltration and extravasation in earlier stages. Alternatively, the use of technologies including ultrasound may be useful for early detection of infiltration and extravasation [68]. A study of PIVC failure in adults found that 9.7% of participants presented with subcutaneous edema on clinical exam, versus 56.5% of participants based on ultra sonographic evaluation [18].…”
Section: Diagnosismentioning
confidence: 99%
“…One of the leading complications associated with PIVCs is peripheral intravenous infiltration/extravasation (PIVIE), with long periods of minimally impactful innovations that protect the patient from this form of associated injury. Most importantly is the early identification of PIVIE, which also has been discussed by the authors . In many clinical situations, extravasation may be from several clinical aspects: posterior vessel wall puncture, increased vein porosity, catheter lumen rupture (from excessive pressure or power injection procedures), or unexpected device failure, all of which share a common element, infiltration into the surrounding subcutaneous tissue.…”
mentioning
confidence: 99%
“…We recently read with interest the publication from Hirata and colleagues who discussed extravasation and its associated mechanisms of applied sensing monitoring technologies for preventative strategies with intravascular devices. While the authors mentioned the basic procedural aspects of venous cannulation, they additionally could have discussed more widely accepted technologies for device placement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We recently received and checked your Comment about our latest Review in ACS Sensors entitled “Sensing Technologies for Extravasation Detection: A Review” 1 and we appreciate the interest it has generated in the scientific community.…”
mentioning
confidence: 99%